Experimental studies on gas production rate of in-situ hydrate-bearing clay in thermal recovery and depressurization methods. (February 2019) - Luo, Tingting; Li, Yanghui; Liu, Weiguo; Song, Yongchen
Abstract: To understand the gas production characteristics from hydrate-bearing clay (HBC) under certain effective stress by thermal recovery method and depressurization method are significant for recovering natural gas from hydrate reservoirs. In this study, in-situ HBC was shaped in "excess gas method", and the gas production rate of HBC under certain mean effective stress in thermal recovery method and depressurization method was investigated using a hydrate triaxial apparatus. Gas production rate highly depends on the decomposition temperature, high temperature would significantly boost the hydrate decomposition from HBC in the same mean effective stress. The hydrate saturation shows negligible effect on the gas production rate in the main decomposition stage, however, higher mean effective stress would reduce the gas production rate by preventing the gas discharge. Besides, the depressurization range plays a dominant role in the gas production rate, higher depressurization range would bring about higher gas production rate in higher mean effective stress. In addition, it's proved that depressurization method is more effective and available than thermal recovery method for gas production from HBC.